Conjunctival and Lingual mucosal neuromas without multiple endocrine neoplasia type 2B - Talia N. Shoshany; Christopher J. Rapuano; Tatyana Milman (American Journal of Ophthalmology Case Reports, 2023)
Purpose: To report a patient with conjunctival and buccal neuromas and enlarged corneal nerves without Multiple Endocrine Neoplasia 2B (MEN2B). Observations: A 28-year-old female presented with progressively enlarging bilateral limbal conjunctival growths. Slit lamp examination was notable for enlarged corneal nerves and well-circumscribed gelatinous subepithelial limbal nodules. Systemic examination revealed similar lesions on the tongue. Conjunctival biopsy demonstrated a mucosal neuroma. The patient underwent endocrine workup for MEN2B and genetic testing for the RET-proto oncogene mutations, all of which were negative. Conclusions and Importance: The findings in our patient may be compatible with pure mucosal neuroma syndrome. The pattern of conjunctival neuromas and enlarged corneal nerves should raise concern for MEN2B, a hereditary tumor predisposition syndrome with almost 100% incidence of medullary thyroid cancer, unless prophylactic thyroidectomy is performed. Accurate diagnosis and prompt referral for endocrine and genetic testing is critical. Isolated mucosal neuromas without endocrine manifestations of MEN2B can rarely occur in a “pure mucosal neuroma syndrome,” which is a diagnosis of exclusion in a setting of a negative workup.